Подход к вероятностной оценке качества результатов функционирования систем «человек - машина» - Лавров, Е. А.; Барченко, Н. Л. (Eastern-European Journal of Enterprise Technologies, 2020)
Developing an approach to building a model estimating the probability that the functional algorithms of discrete systems ”man-machine” with different levels of quality. The development of the previously known approaches lies in the empowerment model functional models and the rejection of traditional interpretation conception of ”error” and ”infallibility”. The efficiency of the approach is demonstrated by the example of the type functional structure ”working control operation”